Learn to relax: ease tension conquer stress free the self - "George, Mike" (London, 1998)
George includes 25 step-by-step exercises designed to take the stresses out of life and maximise the quality of leisure, as well as providing techniques for awakening your sense and converting negative to positive.
Keywords: Stress